Development of a Digital Platform through E-catalog for Information Dissemination - saffira wardhana; Iwan Hermawan; Azizah (Jurnal Teknologi dan Terapan Bisnis, 2023)
Information technology, especially the internet, plays a crucial role in enabling fast business growth through promotions, operational efficiency, cost reduction, and increased sales. Digitalization has become essential for businesses, and one of its innovations is the development of a website-based e-catalog, providing digital access to entities, services, specifications, brands, technical details, prices, and quantities available. This research aims to construct a website-based e-catalog using the Waterfall method, a systematic and sequential approach to software development, starting from user requirements specification, followed by planning, modeling, construction, deployment, and maintenance. The implementation of the e-catalog at PT Uola Pandawa Sejahtera is expected to optimize information dissemination, facilitating customer access to essential details. It is anticipated that this innovation will improve employee flexibility in updating information and reduce costs associated with traditional printed catalogs. The contribution of this research lies in enhancing PT Uola Pandawa Sejahtera's services and reducing costs, ultimately supporting their competitiveness in the global market driven by digital technology.